Lamb-Wave Based Structural Health Monitoring in Polymer Composites - Lammering, Rolf.; Gabbert, Ulrich; Sinapius, Michael; Schuster, Thomas; Wierach, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The book focuses especially on the application of SHM technology to thin walled structural systems made from carbon fiber reinforced plastics. Here, guided elastic waves (Lamb-waves) show an excellent sensitivity to structural damages so that they are in the center of this book. It is divided into 4 sections dealing with analytical, numerical and experimental fundamentals, and subsequently with Lamb-wave propagation in fiber reinforced composites, SHM-systems and signal processing. The book is designed for engineering students as well as for researchers in the field of structural health monitoring and for users of this technology.
Keywords: Mechanical Engineering; Solid Mechanics; Ceramics, Glass, Composites, Natural Materials; Aerospace Technology and Astronautics